Citrus Diseases Exotic to Florida: Citrus Variegated Chlorosis (CVC) - Kuang Ren Chung; Ronald H. Brlansky (EDIS)
This paper discusses a disease caused by a xylem inhibiting bacterium, Citrus Variegated Chlorosis (CVC). This document is Fact Sheet PP-223, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date: October 2005.